Keeping the master cool, every day, all day: Punkah-pulling in colonial India. (January 2022) - Sengupta, Ritam
This article studies how the distribution of the work of punkah-pulling in European households and barracks of colonial India involved European masters making gradually multiplying claims on their servants' labouring time and how these claims fared in practice. The laborious task of punkah-pulling in such establishments was often resisted by native servants on counts of caste, custom or simply exhaustion. In the context of such conflicts, this article tries to understand how the colonial state and its legal and regulatory functions mediated the contested terrain of domestic and service work over the nineteenth century. Over the latter half of this century, punkah-pulling became a separate occupation, even as this occupation slid down the hierarchy of service work and became a more pronounced target of recurring racial violence. Against this background, the article also tries to grapple with the material limits encountered by the regimes of work involved in the cheap, day-and-night conduct of punkah-pulling that eventually led up to the acceptance of mechanised alternatives.